SOLAR ENERGY IN RURAL AREAS: POTENTIAL AND CHALLENGES (TRAKIA JOURNAL OF SCIENCES, 2025)
The green transition is a key global focus, and solar energy has a significant potential for transforming rural areas by providing sustainable and decentralized resolutions. Analyzing the renewable energy implementation opportunities could help develop sustainable trajectories for the future of renewables most suitable in each region. This survey applies a policy-oriented methodology to explore the key factors and links, influencing of solar energy. The paper aims to observe the potential of renewable energy sources in the EU’s rural areas, focusing on solar energy in Bulgaria. The results indicate that the EU contains substantial yet underutilized capacity for renewable energy expansion, which could be effectively achieved while maintaining a balance between energy transition goals, environmental and agricultural sustainability. In addition, local communities in rural areas are crucial drivers for building and promoting renewable energy. However, despite its potential, the adoption of solar energy in rural areas faces a number of challenges, such as high initial investment costs, infrastructure issues and regulatory barriers. By addressing existing obstacles, governments and stakeholders can unlock the benefits of solar energy, contributing to resilience, sustainability, and better employment opportunities in rural communities.